Automatic Recognition of Chinese Personal Name Using Conditional Random Fields and Knowledge Base. (4th October 2015) - Gu, Chuan; Tian, Xi-ping; Yu, Jiang-de
Abstract : According to the features of Chinese personal name, we present an approach for Chinese personal name recognition based on conditional random fields (CRF) and knowledge base in this paper. The method builds multiple features of CRF model by adopting Chinese character as processing unit, selects useful features based on selection algorithm of knowledge base and incremental feature template, and finally implements the automatic recognition of Chinese personal name from Chinese document. The experimental results on open real corpus demonstrated the effectiveness of our method and obtained high accuracy rate and high recall rate of recognition.